2016
DOI: 10.1136/annrheumdis-2015-208456
|View full text |Cite
|
Sign up to set email alerts
|

Autologous tolerogenic dendritic cells for rheumatoid and inflammatory arthritis

Abstract: ObjectivesTo assess the safety of intra-articular (IA) autologous tolerogenic dendritic cells (tolDC) in patients with inflammatory arthritis and an inflamed knee; to assess the feasibility and acceptability of the approach and to assess potential effects on local and systemic disease activities.MethodsAn unblinded, randomised, controlled, dose escalation Phase I trial. TolDC were differentiated from CD14+ monocytes and loaded with autologous synovial fluid as a source of autoantigens. Cohorts of three partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
222
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(228 citation statements)
references
References 22 publications
1
222
0
5
Order By: Relevance
“…In support of this concept, a phase I clinical trial demonstrated improvement in DAS28 in RA patients transfused with autologous tolerogenic DCs modified in vitro with an NF-kB inhibitor51, and this was associated with a decrease in antigen-specific effector T cells and serum pro-inflammatory cytokines, and an increase in regulatory T cells. A similar study with intra-articular delivery of autologous tolerogenic DCs showed stabilization of knee symptoms52. Thus, a better understanding of the regulatory mechanisms operating in DCs of RA could help development next generation DC-based therapies.…”
Section: Discussionmentioning
confidence: 77%
“…In support of this concept, a phase I clinical trial demonstrated improvement in DAS28 in RA patients transfused with autologous tolerogenic DCs modified in vitro with an NF-kB inhibitor51, and this was associated with a decrease in antigen-specific effector T cells and serum pro-inflammatory cytokines, and an increase in regulatory T cells. A similar study with intra-articular delivery of autologous tolerogenic DCs showed stabilization of knee symptoms52. Thus, a better understanding of the regulatory mechanisms operating in DCs of RA could help development next generation DC-based therapies.…”
Section: Discussionmentioning
confidence: 77%
“…Another attempt has been performed in RA patients by using autologous DC generated in the presence of Dex and VitD3 and pulsed with synovial fluid (named AutoDECRA, ClinicalTrials.gov identifier NCT01352858) and then injected into the inflamed joints. Two out of nine patients treated with this approach showed stabilization of the local symptoms but not systemic clinic improvements [250]. The potential therapeutic administration of autologous DC pulsed with self-antigen involved in SLE pathogenesis, such as nucleosomes, Ro, La, and Sm is under investigations [251e253].…”
Section: Targeting In Human Autoimmune Diseasesmentioning
confidence: 99%
“…Application of TolDCs for RA treatment has been successfully tested in animal models (23, 24). Phase I clinical trials using in vitro modified autologous TolDCs demonstrated feasibility and safety in patients with type 1 diabetes (25) and RA (15, 26). …”
Section: Introductionmentioning
confidence: 99%